APEC and liberalisation of the Chinese economy - Drysdale, Peter; Yunling, Zhang; Song, Ligang (ANU Press, 2012)
"China is so large that its trading interests and influence are global. But its interests are disproportionately powerful in its immediate Western Pacific and Asia Pacific partners. The evolution of China's economic relationships with its Asia Pacific partners, in which APEC came to play a significant role in the 1990s, is thus a central part of the story of China's rapidly growing and changing interaction with the global economy." - Ross Garnaut APEC is an important forum thorugh which China can demonstrate its commitment to economic openness. APEC has also been an important vehicle for China's trade liberalisation on the way towards accession to the WTO. In facilitating trade liberalisation, APEC and te WTO are mutually reinforcing. APEC prepares China for the WTO and WTO accession encourages China's active participation in the APEC process. Both APEC membership and WTO accession help with the huge task of China's domestic reform. This book sets out China's strategic interests in APEC in the lead-up to the APEC summit in Shanghai in 2001. Contributors include leading Chinese economists from the APEC Policy Research Centre in the Chinese Academy of Social Sciences-Zhang Yunling, Zhang Jianjun, Sun Xuegong, Li Kai, Chen Luzhi, Zhou Xiaobing, Zhao Jianglin-and from the Asia Pacific School of Economics and Management at The Australian National University-Peter Drysdale, Ligang Song, Ross Garnaut, hristopher Findlay, Andrew Elek, Yongzheng Yang, Yiping Huang, K.P. Kalirajan, Hadi Soesastro and Chen Chunlai.